2015
DOI: 10.1016/j.fuel.2015.06.070
|View full text |Cite
|
Sign up to set email alerts
|

Laminar burning velocity and Markstein length of ammonia/air premixed flames at various pressures

Abstract: h i g h l i g h t sLaminar burning velocities of ammonia/air flames at high pressures are evaluated. Maximum value of laminar burning velocity of ammonia/air flame is about 7 cm/s. Laminar burning velocity decreases with the increase in the pressure. Markstein length increases with the increase in equivalence ratio. Markstein lengths at high pressure are lower than those at 0.1 MPa. a b s t r a c tAmmonia is expected to be useful not only as a hydrogen-energy carrier but also as a carbon-free fuel. In order to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
210
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 521 publications
(234 citation statements)
references
References 28 publications
13
210
1
3
Order By: Relevance
“…Recently, ammonia has attracted interest as a potential carbon-free energy carrier [5]. Results on oxidation of NH 3 are available from flames [6][7][8][9][10][11][12][13][14][15][16], shock tubes [17][18][19][20][21][22][23][24][25][26][27], and flow reactors [2,[28][29][30]. In addition, a number of modeling studies and reviews of ammonia chemistry have been reported [3,27,28,[31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, ammonia has attracted interest as a potential carbon-free energy carrier [5]. Results on oxidation of NH 3 are available from flames [6][7][8][9][10][11][12][13][14][15][16], shock tubes [17][18][19][20][21][22][23][24][25][26][27], and flow reactors [2,[28][29][30]. In addition, a number of modeling studies and reviews of ammonia chemistry have been reported [3,27,28,[31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…High-temperature results at increased pressure are available from recent work in shock tubes and premixed flames. Mathieu and Petersen [27] measured the ignition time for ammonia diluted in Ar at 1.4, 11, and 30 bar, respectively, while Hayakawa et al [15] determined the burning velocity of ammonia/air mixtures at pressures of 1-5 bar. However, studies of ammonia oxidation at low-to-medium temperatures and high pressure are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the lack of experimental data in the literature for the previously-mentioned conditions and mixture compositions, an indirect approach is applied in order to validate the computations. In total, 31 experimental datasets from the literature [58,[61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78] are used, as depicted in Table 3, in order to validate the chosen mechanisms (Table 2) at atmospheric conditions, as well as at elevated temperatures (up to 2085 K) and pressures (up to 5.1 MPa). The validation results are shown in Figure 4.…”
Section: Comparison Of Fundamental Combustion Propertiesmentioning
confidence: 99%
“…近年,欧米をはじめとする諸外国を中心にアンモニアを代替燃料とするための研究が行われている (Zamfirescu and Dincer, 2008, Takizawa et al, 2008, Ronny, 1988, Kumar and Meyer, 2013, Duynslaegher et al, 2009, Duynslaegher et al, 2010, Pfahl et al, 2000, Li et al, 2014, Hayakawa et al, 2015a, Hayakawa et al, 2015b, Ichikawa et al, 2015, 武石他, 2015, 武石他, 2016, 小林, 早川, 2016, 小池他, 2016, 武石他, 2017 (水谷, 矢野, 1978, Chung and Lee, 1991, Takahashi and Schmoll, 1990, 小谷他, 2004, Otakeyama et al, 2009 …”
Section: 緒 言unclassified